Lincoln : an intimate portrait. - Guelzo, Allen C.; Gates, Henry Louis, Jr (Life Books, 2014)
On the 150th anniversary of Abraham Lincoln's assassination, the editors of Life bring readers everything that has been left to us from the life of one of history's most iconic figures. His pictures, actions, words in his speeches and his private letters are analyzed and pointed inward toward the person, to help us understand the man: the heart and soul of the man. This book is about the artifacts that are left us all these years later (letters, speeches and particularly pictures) --things that LIFE can show that allow us to know this man more intimately. And so we, with help from experts and several famous commentators, will show them in our pages, and lead the reader to the clues about Lincoln's essence.